(untitled) (Scientific journal of the Fergana State University, 2025)
The silk industry of Uzbekistan is one of the important sectors of the economic and social life of the country. This study analyzed the features, history of development, significance and socio-economic aspects of the silk industry in Uzbekistan. Uzbekistan is one of the world’s leading silk producing countries and plays an important role in the country’s agricultural and export potential. The silk industry has a great influence not only economically, but also in the social sphere, since this industry creates jobs for thousands of families, helps improve the living conditions of the population in rural areas, and has its own cultural and national significance. This study examines economic growth, technological innovation, export strategies and socio-economic impact of sericulture, and the role of government policy in the development of this industry. The study is aimed at an in-depth analysis of the future prospects of the silk industry in Uzbekistan, its place in world markets and its contribution to the domestic economy.